Constructing C-rich polymeric carbon nitride homojunctions for enhanced storage capacity of photo-rechargeable batteries. (1st June 2023) - Wang, X.H.; Tang, X.; Liu, T.T.; Li, Y.H.; Ling, F.L.; Jing, C.; Yao, L.; Zhou, X.J.; Xiang, G.T.
Abstract: The light-induced accumulation of long-lived trapped electrons within the conjugated heptazine backbone enables polymeric carbon nitrides the dual ability of light absorption and charge storage. However, the storage capacity has still been plagued by the severe recombination of photoinduced electrons and holes. Carbon-rich polymeric carbon nitrides (CPCN) with the conjugated backbone combining heptazine motifs and individual aromatic nucleus have tunable energy band structure. Herein, in order to enhance the photo-rechargeable capacity, we present a type-II homojunction constructed by two CPCN monolayer materials with different bandgaps and band-edges to build the band bending for charge separation. The desirable hole-extraction route for the CPCN photo-rechargeable solar cell is revealed and a remarkable high record of photo-charging capacity of 486 C g −1 is achieved. The microstructure of the CPCN materials are characterized by XPS, NMR, UPS and UV-Vis. The photoelectrochemical properties of the CPCN monolayer and homojunction photoelectrodes are investigated using cyclic voltammetry (CV), Electrochemical impedance spectroscopy (EIS) and Mott-Schottky method.